Discrete Survival Time Constructions for Studying Marital Formation and Dissolution in Rural South Africa - Batidzirai, Jesca M.; Manda, Samuel O. M.; Mwambi, Henry G.; Tanser, Frank (Frontiers in Psychology, 2020)
Introduction: Marriage formation and dissolution are important life-course events which impact psychological well-being and health of adults and children experiencing the events. Family studies have usually concentrated on analyzing single transitions including Never Married to Married and Married to Divorced. This does not allow understanding and interrogation of dynamics of these life changing events and their effects on individuals and their families. The objective of this study was to assess determinants associated with transitions between and within marital states in South Africa. Methods: The population-based data available for this study consists of over 55 000 subjects representing over 340 000 person- years exposure from the Africa Health Research Institute (AHRI) in rural KwaZulu-Natal, South Africa. It was collected from 1 January 2004 to 31 December 2016. Multilevel multinomial, binary and competing risks regression models were used to model marital state occupation, transitions between marital states as well as investigate determinants of marital dissolution, respectively. Results: After 2007, subjects were less likely to be married than never married and the trend reduced over the years up to 2016. In 2008-2009, subjects were more likely to experience a marital dissolution than in the period 2004-2005 and the trend slightly reduces from 2010 until 2013. (OR = 24:49;CI = (5:53; 108:37)). Raising age at first sexual debut was found to be inversely associated with a marital dissolution (OR = 0:97;CI = (0:95; 0:99)). Highly educated subjects were more likely to stay in one marital state than those who never went to school (OR = 6:43;CI = (4:89; 8:47);OR = 18:86;CI = (1:14; 53:31) and OR = 2:96;CI = (1:96; 4:46) for being married, separated and widowed, respectively, among subjects with tertiary education). Conclusion: The study found that raising the age at first marriage had a negative impact on the rate of marital dissolution while more educated subjects tend to stay in one marital state. Increasing age at sexual debut was associated with a lower likelihood of experiencing a marital dissolution. Our findings suggests that programs encouraging delay marriage would have a positive impact in lowering marital dissolution, thus improving psychological and physical health.